From “religion” to “spirituality” in socialist Bulgaria: Vanga, Nicholas Roerich, and the mystique of history - Valtchinova Galia (Balcanica)
The article delves into processes unfolding in Bulgaria in the 1970s, centring around two figures: Vanga, known as the seer of Petrič, and the mystic painter Nicholas Roerich, to demonstrate the changes in the structure and meaning of categories related to religion that occurred in the period of “mature socialism”. The first section looks into the activities of the clairvoyant Vanga and her changing status to uncover the gradual process that transformed her from a local vračka (healer/witch) into the “Bulgarian Pythia”. The second and longest section is dedicated to the Nicholas Roerich Program of 1978, promoted at the highest level in the framework of the celebration of 1300 years of the Bulgarian state, and its impact on coining a peculiar concept of spirituality. The third and final part explores the links between Roerich, Vanga, the notion of spirituality, and a certain vision of history.